2015
DOI: 10.1111/trf.13106
|View full text |Cite
|
Sign up to set email alerts
|

Failure of self‐disclosure of deferrable risk behaviors associated with transfusion‐transmissible infections in blood donors

Abstract: BACKGROUNDTo date, most studies on deferral of blood donors have focused on men who have sex with men (MSM) and/or injecting drug users. Few have examined deferrable risk behaviors relating to transfusion-transmissible infections (TTIs) in general. This study aimed to examine the prevalence of, and factors associated with, nondisclosure of TTI-related risk behaviors in donors.STUDY DESIGN AND METHODSChinese-speaking donors who had just given blood in Hong Kong were invited to self-complete an anonymous questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 39 publications
(77 reference statements)
2
19
0
Order By: Relevance
“…We may have increased the validity of our measurement by defining a test‐seeking index, which combined the above question with other factors influencing donors' decision to donate blood. The test‐seeking rates reported here are not substantially different than previous reports in the general donor population or among donors with HIV infection, regardless of how test‐seeking information was obtained.…”
Section: Discussionsupporting
confidence: 88%
“…We may have increased the validity of our measurement by defining a test‐seeking index, which combined the above question with other factors influencing donors' decision to donate blood. The test‐seeking rates reported here are not substantially different than previous reports in the general donor population or among donors with HIV infection, regardless of how test‐seeking information was obtained.…”
Section: Discussionsupporting
confidence: 88%
“…We found that the non-compliance rate of donors with deferrable non-MSM behavioural risk was 2Á6%, a figure somewhat higher than that of 1Á2% for MSM in male donors. The latter prevalence was similar to the result of a previous survey (1Á5%), we conducted in Hong Kong over 4 years ago [11], and comparable to <0Á5% to 3% in other overseas studies [10,12]. It is hard to compare the prevalence of MSM-unrelated deferrable risk between cities/countries as similar studies in the literature are limited.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, adding an "unsure" option on the DHQ could provide donors the possibility to discuss their uncertainty with Blood Service employees and not be forced to choose between "yes" or "no." 31 It is possible that the ambivalence in definitions may also apply to a wider range of sexual (deferrable) behaviors. Our results also suggest that blood services need to explain better why it is important that donors are truthful in their answers.…”
Section: Discussionmentioning
confidence: 99%